The Prosthodontics Care For Geriatric Patients Nowadays - Indriani Oktaria; Robert Shen (Journal of Indonesian Dental Association, 2019)
The global geriatric (elderly) population is growing as a result of increasing life expectancies. One impact of this development is an increase of lifestyle difference. In the scope of health, especially dental health, the patient’s education is important. The decrease in edentulism cases showsed public awareness of the importance in maintaining the health, function and quality of life in the elderly as well as the necessity of preventive attitudes and interventions against disease. Dental services for geriatric patients are affected by the cost of dental services, dental insurance, dental clinics’ access, debt and needs. The current prosthodontic treatment that improve of missing tooth replacements is in demand is an increasing interest in dental implant treatment. Losing tooth has a negative impact on mastication, aesthetic- and oral health-related quality of life. Excessive bone resorption can occur for many reasons, including age, infection, trauma, metabolic disorders and nutritional deficiencies. The resorption of the alveolar bone, especially in medically compromised patients, is caused by focal infections in the mouth and systemic diseases. Periodontitis or other chronic infections resulted from bacterial and host inflammatory cells. The pathology observation can result in a loss of bone support after a long period of extraction procedures is named residual ridge resorption (RRR). The best treatment for RRR is to avoid tooth extraction so that the loss of teeth and their supportive tissues can be prevented. When there is a loss of teeth and RRR, dentures have been made to reduce the occlusal load are necessary. In addition, the importance of periodic control, utilizing vitamins, oral rinse, topical gels or others, and the intake of nutrients greatly affect the good function of dentures and improve the health of the geriatric patient.